Management Desa Sukomulyo: Potensi Menjadi Desa Wisata di Destinasi Pariwisata Super Prioritas Borobudur - Emik Rahayu; Joseph Aldo Irawan; Izza Ulumuddin Ahmad Asshofi; Sudiana Wachyudi; Fitriatunnisa Shabrina; Andi Hallang Lewa (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Sukomulyo Village, a village around Borobudur's Super Priority Tourism Destination, wants to develop into a tourist destination. The correct form of tourist destination is to become a tourist village. Efforts to become a tourist village are certainly a challenging thing. It is necessary to conduct research first to find out the village's potential so that it can declare it to be a tourist village because it has adequate facilities. To achieve the goal, cooperation efforts are needed between the village government and the villagers to create synergy in understanding. In addition, it is necessary to explore the potential of Sukomulyo village to determine its readiness to become a tourist village. This research uses qualitative descriptive methods through field observations and interview discussions. The purpose of this study is to describe the efforts of Sukomulyo village to become a new tourist village around the Super Priority Tourism Destination of Borobudur and produce tour packages. The results of this study show that the potential of Sukomulyo village can be designed as a strategy to become a tourist village to attract potential tourists.